Nutritional characteristics and clinical outcomes of critically ill patients with and without diabetes mellitus: a single-center prospective observational study in Malaysia - Lee, Zheng Yii; Ibrahim, Noor Airini; Osama, Hamdy; Mohd Yusof, Barakatun Nisak (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: This study aimed to compare the nutritional characteristics and clinical outcomes among critically ill patients with diabetes (DM) and without diabetes (WDM). Methods: Mechanically ventilated, critically ill patients who were admitted into the intensive care unit (ICU) within 48 hours and remained in ICU ≥72 hours were prospectively recruited and followed for up to 12 days. They were stratified to DM or WDM, depending on their diabetes status at ICU admission and comparison were made for nutritional characteristics and clinical outcomes including 60-day mortality. Results: A total of 154 patients were included with 73 (47.4%) DM patients. In comparison to WDM, patients with DM were older, more severely ill, had higher nutritional risk and body mass index, presented with a higher blood glucose level, and required more insulin. DM was fed relatively earlier but had lower energy adequacy. They experienced more frequent EN interruption. Both groups had comparable ICU and hospital stay, ventilation support duration and mortality. In multivariable logistic regression, no association was found between diabetes status and for ICU and hospital mortality. However, There was a trend towards an increase in 60-day mortality in DM patients (Odds Ratio: 2.220, 95% Confidence Interval: 0.764-6.452; p=0.143). Conclusion: Critically ill patients with DM had higher nutritional risks, were fed relatively earlier, but with frequent EN interruption leading to lower energy adequacy than patients WDM. Diabetes status does not affect clinical outcomes.